2023
DOI: 10.3390/ani13111744
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mutation in the Feline NPC2 Gene in Cats with Niemann–Pick Disease

Abstract: Niemann–Pick disease (NP) type C is an autosomal, recessive, and inherited neurovisceral genetic disorder characterized by the accumulation of unesterified cholesterol and glycolipids in cellular lysosomes and late endosomes, with a wide spectrum of clinical phenotypes. This study aimed to determine the molecular genetic alterations in two cases of felines with NP in Japan, a Siamese cat in 1989 and a Japanese domestic (JD) cat in 1998. Sanger sequencing was performed on 25 exons of the feline NPC1 gene and 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Its coding protein NPC2 (NPC intracellular cholesterol transporter 2) is a protein coding gene containing a lipid recognition domain, which has been proved to play an important role in biological processes such as cholesterol metabolism [19] . Some studies have found that the mutation of this gene is associated with thyroid cancer [20] , gastric cancer [21] and Niemann-pick disease [22] . In order to further clarify the relationship between NPC2 gene and GBM and to guide the prognosis of GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Its coding protein NPC2 (NPC intracellular cholesterol transporter 2) is a protein coding gene containing a lipid recognition domain, which has been proved to play an important role in biological processes such as cholesterol metabolism [19] . Some studies have found that the mutation of this gene is associated with thyroid cancer [20] , gastric cancer [21] and Niemann-pick disease [22] . In order to further clarify the relationship between NPC2 gene and GBM and to guide the prognosis of GBM.…”
Section: Discussionmentioning
confidence: 99%